Regulating Protein Corona Formation and Dynamic Protein Exchange by Controlling Nanoparticle Hydrophobicity - Yu, Qianhui; Zhao, Linxia; Guo, Congcong; Yan, Bing; Su, Gaoxing (Frontiers in Bioengineering and Biotechnology, 2020)
Physiochemical properties of engineered nanoparticles (NPs) play a vital role in nano-bio interactions, which are critical for nanotoxicity and nanomedicine research. To understand the effects of NP hydrophobicity on the formation of the protein corona, we synthesized four gold NPs with a continuous change in hydrophobicity ranging from -2.6 to 2.4. Hydrophobic NPs adsorbed 2.1-fold proteins compared to hydrophilic ones. Proteins with small molecular weights (< 50 kDa) and negatively charge (PI < 7) constituted the majority of the protein corona, especially for hydrophobic NPs. Moreover, proteins preferred binding to hydrophilic NPs (vitronectin and antithrombin III), hydrophobic NPs (serum albumin and hemoglobin fetal subunit beta), and medium hydrophobic NPs (talin 1 and prothrombin) were identified. Besides, proteins such as apolipoprotein bound to all NPs, did not show surface preference. We also found that there was a dynamic exchange between hard protein corona and solution proteins. Because of such dynamic exchanges, protein-bound NPs could expose their surface in biological systems. Hydrophilic NPs exhibited higher protein exchange rate than hydrophobic NPs. Above understandings have improved our capabilities to modulate protein corona formation by controlling surface chemistry of NPs. These will also help modulate nanotoxicity and develop better nanomedcines.